1961
DOI: 10.1111/j.1532-5415.1961.tb00427.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychologic Studies in Neurologic Diseases—a Review: Parkinson's Disease and Multiple Sclerosis*

Abstract: Parkinson's disease and multiple sclerosis (hereafter referred to as P.D. and M.S. respectively) represent progressive chronic diseases of the central nervous system. A large proportion of the afflicted persons fall within the geriatric population. In each instance, the disease may result in alterations of the motor and sensory systems of the brain and spinal cord, and thus produce various abnormalities of movement and sensation. The specific et,iology in both diseases is largely unknown (although continuing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1995
1995

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Few if any conclusions can be drawn from these studies concerning psychological issues in MS. Reviews of early psychoanalytic literature can be found in Riklan, Levita, and Diller (1961), Philippopoulos, Wittkower, and Cousineau (1958), Surridge (1969), andAcheson (1965).…”
Section: Research On Psychological Aspects Of Msmentioning
confidence: 99%
“…Few if any conclusions can be drawn from these studies concerning psychological issues in MS. Reviews of early psychoanalytic literature can be found in Riklan, Levita, and Diller (1961), Philippopoulos, Wittkower, and Cousineau (1958), Surridge (1969), andAcheson (1965).…”
Section: Research On Psychological Aspects Of Msmentioning
confidence: 99%